2015
DOI: 10.1016/j.plantsci.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Some rootstocks improve pepper tolerance to mild salinity through ionic regulation

Abstract: Elsevier Penella, C.; González Nebauer, S.; Quinones, A.; San Bautista Primo, A.; López Galarza, SV.; Calatayud, A. (2015). Some rootstocks improve pepper tolerance to mild salinity through ionic regulation. Plant Science. 230:12-22. doi:10.1016Science. 230:12-22. doi:10. /j.plantsci.2014 . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 76 publications
11
60
1
Order By: Relevance
“…The selection of salt tolerant accessions to be used as rootstocks could be a promising approach to ameliorate the negative effects of salinity on pepper productivity (Penella et al, 2013;Penella et al, 2015). In the present study, we demonstrated that Adige peppers grafted onto the accession A25 were less sensitive to salt stress compared to their ungrafted counterparts.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…The selection of salt tolerant accessions to be used as rootstocks could be a promising approach to ameliorate the negative effects of salinity on pepper productivity (Penella et al, 2013;Penella et al, 2015). In the present study, we demonstrated that Adige peppers grafted onto the accession A25 were less sensitive to salt stress compared to their ungrafted counterparts.…”
Section: Discussionsupporting
confidence: 50%
“…Maintenance of shoot and root vigor is dependent mainly on photosynthetic capacity (Duarte et al, 2014;Penella et al, 2015). Photosynthetic activity remained unchanged in A/A25 plants under salt conditions compared to their controls and, therefore, also in the supply of photosynthates to plants, as confirmed by the absence of reduced plant growth.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations